Gel material based on azeotropic solvent and cooling patch
By using azeotropic solvent and high thermal conductivity fillers in the hydrogel cooling patch, the cooling efficiency is improved, and the existing hydrogel cooling patch has been solved, thereby achieving a faster and more efficient cooling effect.
Patent Information
- Application Number
- CN202411732506.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The cooling range of existing hydrogel cooling patches is limited and cannot effectively reduce the internal temperature of the human body, especially in the case of high heat or continuous heating.
A gel-based material based on azeotropic solvent is used to increase the volatility by a solvent azeotropic with water instead of a separate water solvent, and add high thermal conductivity thermal fillers to the material to form a fast heat conduction channel.
It significantly improves the cooling efficiency of the cooling patch, and can reduce the temperature by more than 8 degrees within 2 minutes, solving the problem of limited cooling range of the hydrogel cooling patch.
Smart Images

Figure CN119552466A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gel functional materials, and particularly relates to a gel material based on an azeotropic solvent, and a cooling patch developed based on the material. Background Art
[0002] Hydrogel is a type of extremely hydrophilic three-dimensional network structure gel. The aggregated state of this gel is neither completely solid nor completely liquid, but a special state between the two. In addition, hydrogel has good softness and plasticity, and can adapt to various shapes and surface requirements. Hydrogels can be divided into physical gels and chemical gels according to the different network bonding. Physical gels are formed by physical forces, such as electrostatic effects, hydrogen bonds, chain entanglement, etc. This type of gel is non-permanent. Chemical gels are three-dimensional network polymers formed by cross-linking chemical bonds, which are permanent. In addition, according to the response of hydrogels to external stimuli, they can also be divided into two categories: traditional hydrogels and environmentally sensitive hydrogels.
[0003] The raw materials of hydrogels can be natural or synthetic. The raw materials of natural polymer hydrogels mainly include gelatin, chitosan, sodium alginate, collagen, etc. Most of these raw materials come from animal tissues or marine organisms, so they have the characteristics of good biocompatibility and degradability. However, the mechanical properties of natural polymer hydrogels are low and cannot meet the requirements of certain applications. Synthetic polymer hydrogels are polymers obtained by polymerization reactions of synthetic materials, such as polyacrylamide and polyethylene glycol. These hydrogels have the characteristics of structural controllability, good repeatability and excellent mechanical properties. As a highly water-absorbing and water-retaining material, hydrogels are widely used in many fields. In the agricultural field, hydrogels can be used as soil conditioners to improve the water retention capacity of soil and promote crop growth. In the medical field, hydrogels are used as drug delivery systems, wound dressings and tissue engineering scaffolds, etc., and have broad application prospects. In addition, hydrogels are also used in cosmetics, personal care products, coatings, environmental protection, textiles and other fields.
[0004] The hydrogel cooling patch is a new device based on hydrogel. It uses the large amount of water contained in the polymer gel to achieve the effect of lowering body temperature through the physical change of water volatilization and heat absorption. This cooling method belongs to physical cooling, without drug stimulation, so it has the characteristics of high safety and small side effects. The hydrogel cooling patch is usually composed of a backing layer, a gel layer, an anti-adhesive layer and other parts. Among them, the gel layer is the core part, containing menthol, parahydroxybenzoic acid, water, polymer substances, glycerin and other ingredients. These ingredients work together, on the one hand, to enable the hydrogel to quickly absorb and dissipate a large amount of heat, thereby effectively lowering the body temperature, and on the other hand, to stimulate the cold receptors on the skin, so that the human body feels cold. With the advancement of science and technology and the improvement of people's health awareness, the technology of hydrogel cooling patches is also constantly innovating and developing. For example, some new hydrogel cooling patches use more advanced polymer gel materials to improve their water absorption and water retention capabilities; at the same time, more natural plant extracts and other ingredients are added to enhance their cooling effect and comfort. In addition, some hydrogel cooling patches also use unique production processes and sterilization technologies to ensure their safety and effectiveness.
[0005] In summary, as a safe, efficient, convenient and low-cost physical cooling product, the hydrogel cooling patch has broad application prospects in the fields of medical care and home care.
[0006] Although the hydrogel cooling patch can take away heat through water evaporation and achieve a certain cooling effect, its cooling range is usually limited. Since the body temperature of the human body is balanced by blood flow, simply lowering the temperature of the skin surface cannot effectively lower the temperature in the body, especially the temperature of important organs such as the brain. Therefore, for patients with high fever or persistent fever, the hydrogel cooling patch may not provide sufficient cooling effect. Mechanistically, the current hydrogel cooling patch is mainly based on the volatilization of water to take away heat, which is affected by the ambient temperature and humidity. In a low temperature and high humidity environment, the volatilization of water is limited, and the cooling effect is also extremely insignificant. In addition, the thermal conductivity of the hydrogel is low, and the heat generated by the human body cannot be quickly taken away by the hydrogel cooling patch, which will cause the temperature of the hydrogel cooling patch close to the skin to rise, but the heat is difficult to quickly reach the other side, thereby diffusing into the air. Therefore, in order to improve the cooling effect of the hydrogel cooling patch and achieve fast and efficient cooling, it is necessary to solve the two key problems of low water volatilization efficiency in the hydrogel and low thermal conductivity of the material. Summary of the invention
[0007] In view of the two problems of low water volatilization efficiency and low material thermal conductivity of the current hydrogel cooling patch, the present invention proposes a gel material based on an azeotropic solvent, which uses a solvent that azeotropes with water instead of a separate water solvent. The boiling point of the azeotropic solvent is significantly lower than that of water, and the volatility is higher than that of water at the same ambient temperature, so that more heat can be taken away; at the same time, a thermal conductive filler is added to the raw material, and its thermal conductivity is significantly higher than that of the hydrogel, forming a fast channel for heat conduction from the skin to the gel surface, so that the heat on the skin can be quickly brought to the surface of the gel patch and dissipated into the environment. The present invention also discloses a cooling patch made of the above-mentioned gel material, and the cooling patch further has a microscopic rough surface. By increasing the contact area with the air, on the one hand, the volatility of the azeotropic solvent can be increased, and on the other hand, the heat dissipation area can be effectively increased, thereby significantly reducing the temperature of the cooling patch.
[0008] The first aspect of the present invention discloses a gel-like material based on an azeotropic solvent, wherein the gel-like material is formed by solidifying raw materials; the raw materials include an azeotropic solvent and a polymer matrix and a thermal conductive filler dispersed in the azeotropic solvent; the polymer matrix can form a three-dimensional cross-linked network in the azeotropic solvent; the azeotropic solvent is composed of two or more liquids, one of which is water, and the boiling point of the azeotropic solvent is lower than the boiling point of water.
[0009] Optionally, the liquid that forms an azeotropic solvent with water is mainly an organic solvent containing hydroxyl, carboxyl, ketone or ester groups, preferably an organic solvent with low boiling point and low toxicity such as ethanol, n-butanol, isobutanol, ethyl acetate and isopentanol.
[0010] Optionally, the ratio of two or more solvents in the formed azeotropic solvent is preferably the azeotropic point ratio (weight ratio), or additional water is added at the azeotropic point ratio.
[0011] Optionally, the curing methods include cooling curing, heat curing, and light curing; when the curing method is cooling curing, the polymer matrix is selected from polyvinyl alcohol and gelatin materials; when the curing method is heat curing, the polymer matrix is selected from small molecules with epoxy groups; when the curing method is light curing, the polymer matrix is selected from various types of acrylate monomers.
[0012] It is understandable that the polymer matrix is compatible with the solvent and forms a three-dimensional cross-linked network in the solvent. Some polymer matrices, such as polyvinyl alcohol, are made by adding polymer powder to a high-temperature solvent to dissolve it, and then cooling it to room temperature to form a solid gel; some are made by adding polymer precursors, such as small molecules of polyacrylates, to the solvent, and then post-processing such as light curing and heat curing to form polymers, turning liquid into solid gel.
[0013] Optionally, the thermally conductive filler is a material with thermal conductivity, preferably a low-toxic material with high thermal conductivity such as carbon black, silver powder, liquid metal, etc. Among them, the thermal conductivity of high thermal conductivity carbon black is 100W / (m·K), the thermal conductivity of silver powder is 429W / (m·K), and in liquid metal, for example, the thermal conductivity of Ga68In20Sn12 is 39W / (m·K), and the thermal conductivity of Ga68.5In21.5Sn10 is 16.5W / (m·K). In comparison, the thermal conductivity of water is only 0.6W / (m·K).
[0014] Optionally, the additives mainly include a first type of additives for providing a cooling sensation of the gel, and a second type of additives for reducing the evaporation rate of water.
[0015] Optionally, the first type of additives may be menthol, camphor, borneol, etc., and the second type of additives may be water-miscible materials such as glycerol and ethylene glycol. Preferably, both types of additives are added simultaneously, and more than one material may be selected from each type of additive.
[0016] The second aspect of the present invention discloses a cooling patch, which is mainly composed of the gel-like material based on the azeotropic solvent disclosed in the first aspect of the present invention; the gel-like material has a microscopically rough first surface and a second surface arranged opposite to the first surface.
[0017] Optionally, the first surface is made by a template method, and the roughness of the first surface is Ra, 100nm≤Ra≤1000um; the first surface is a regular microstructure array, and the microstructure array can be any one of a hemispherical array, a cylindrical array, a rectangular array, etc.; or the first surface is composed of irregular microstructures. These microstructures can increase the contact area between the gel material and the air, so that the solvent can evaporate more quickly to take away the heat.
[0018] Optionally, the microstructure can be prepared by a template method. First, a template with a reverse microstructure on the surface is prepared by a micro-nano processing method, or a material with a microstructure on the surface is directly used, such as sandpaper, sandblasted stainless steel metal surface, photoresist with a specific structure prepared by micro-nano processing, etc., and a transparent silicone material is used to cast the mold to obtain a silicone template; then the silicone template is covered on the surface of the azeotropic solvent gel precursor liquid, pressurized and cured by cooling, heating or UV light irradiation to obtain a gel material with a microstructure on the surface.
[0019] Optionally, the cooling patch also includes a waterproof packaging material attached to the first surface and the second surface of the gel material. The waterproof packaging material is attached to the upper and lower surfaces of the azeotropic solvent gel and is torn off when in use, so that the solvent in the gel material evaporates and absorbs heat, thereby cooling the material as a whole.
[0020] Optionally, the waterproof packaging material is a material that prevents solvent volatilization, and materials such as polypropylene film and polyethylene terephthalate film can be used.
[0021] The present invention has the following beneficial effects:
[0022] (1) The gel material based on the azeotropic solvent provided by the present invention has a high viscosity and soft elastic properties on the surface, so that the boiling point of the azeotropic solvent is lower than the boiling point of the conventionally used water solvent. Under the same environmental conditions, the solvent of the gel material has a higher volatilization efficiency, so that the heat can be taken away faster, thereby improving the cooling efficiency of the gel. In addition, the azeotropic solvent used in the present invention is mainly water, which can avoid direct irritation of the skin by excessive organic solvents and reduce the volatilization of the odor of the organic solvent.
[0023] (2) The gel material based on azeotropic solvent provided by the present invention contains fillers with high thermal conductivity. The fillers can construct a channel with high thermal conductivity efficiency from the skin to the surface of the gel, thereby bringing the heat on the skin to the surface of the gel for dissipation more quickly.
[0024] (3) The cooling patch made of the gel material described in the present invention has a microscopic rough structure on one side, which can significantly increase the surface area of the gel material and increase the contact area with the air. This not only increases the volatilization rate of the azeotropic solvent, but also increases the heat dissipation area of the cooling patch, thereby significantly improving the cooling efficiency of the cooling patch. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the overall structure of the azeotropic solvent gel cooling patch;
[0026] Figure 2 This is a schematic diagram of the internal microstructure of the azeotropic solvent gel cooling patch;
[0027] Figure labels: 1-cooling patch, 11-microscopic rough structure, 12-thermal conductive filler, 2-skin. DETAILED DESCRIPTION
[0028] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the patent of the present invention. Obviously, the described embodiments are only part of the embodiments of the patent of the present invention, not all of them. Based on the embodiments in the patent of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the patent of the present invention.
[0029] In response to the problem of low cooling efficiency of current hydrogel cooling patches, the patent of this invention proposes a gel material based on azeotropic solvents, and a cooling patch prepared based on this material, which has higher cooling efficiency than hydrogel cooling patches.
[0030] In Example 1, an azeotropic system formed by water and isobutyl alcohol is selected as a solvent, wherein the water content is 80% and the isobutyl alcohol is 20%, both of which are mass ratios. Hydroxyethyl methacrylate and polyethylene glycol 600 acrylate, two small molecules that can be cured by UV light, are selected as polymer matrices, conductive carbon black is selected as a filler, menthol and glycerol are added as additives, and photoinitiator 1173 initiates acrylate curing. Among them, the mass of the azeotropic solvent is taken as 10 parts, 2 parts of hydroxyethyl methacrylate, 0.1 parts of polyethylene glycol 600 acrylate, 2 parts of conductive carbon black, 0.1 parts of menthol, 1 part of glycerol, and 0.05 parts of photoinitiator 1173 are added. After the addition is completed, the mixture is evenly mixed by mechanical stirring to obtain a slurry with a certain viscosity. The slurry is placed in a pre-prepared silicone mold with a 1mm thick rectangular groove to allow the slurry to completely fill the groove, and then covered with a transparent polyethylene terephthalate film on the other side, placed in a UV curing box, and cured at a power of 100mW for 30 minutes. After that, the cured material is taken out of the mold to obtain the desired gel material. The prepared gel material is black, has a smooth surface, has a high viscosity to the skin, and can evaporate quickly in the air. According to measurements, in air at 28 degrees and 50% humidity, the mass of the gel material becomes 77% of the original mass after 1 hour.
[0031] It should be noted that the ratio of the azeotropic point in the present invention refers to the weight ratio. In Example 1, the boiling point of water is 100 degrees, the boiling point of isobutanol is 108 degrees, and the azeotropic point of water and isobutanol is 90 degrees. Under the azeotropic point, water contains 30% and isobutanol 70%, and when volatilizing, it will volatilize first at the azeotropic point ratio. In Example 1, more water is added on the basis of the azeotropic point ratio, which can greatly reduce the smell of isobutanol.
[0032] The gel material prepared in Example 1 can be used to prepare a rapid gel cooling patch based on an azeotropic solvent (referred to as a "rapid cooling patch"). The rapid cooling patch is based on a gel material and has a microscopic rough structure prepared on one side to increase its solvent volatilization rate and heat diffusion efficiency.
[0033] like Figure 1As shown, Example 2 discloses a rapid cooling patch, which is made of the boiling gel described in Example 1. The rapid cooling patch has a microscopic rough structure on one side. When in use, this surface faces away from the skin, usually referred to as the back side; the other side is a smooth surface, which contacts the skin when in use. The microscopic rough structure can be prepared by a template method. In a specific embodiment, the rough structure can be achieved by a silicone template prepared by sandpaper, that is, a silicone precursor is coated on the surface of 100 mesh sandpaper, and the silicone precursor is peeled off after solidification to obtain a silicone template with a microscopic rough structure of the sandpaper surface. The slurry formed by mixing the raw materials of the gel-like material in Example 1 is placed in a silicone mold prepared in advance. The mold has a rectangular groove with a thickness of 1 mm to allow the slurry to completely fill the groove. The silicone template is then covered and a certain pressure is applied to allow the slurry to completely infiltrate the template. The mold is placed in a UV curing box and cured at a power of 100mW for 30 minutes. The cured gel material is then taken out of the mold to obtain the desired hydrogel with a smooth side on one side and a microscopically rough side on the other side, which is the main material for the rapid cooling patch.
[0034] Furthermore, in order to prevent the azeotropic solvent of the gel material from volatilizing when not in use, a polyethylene terephthalate film is attached to the front and back sides of the gel, thereby obtaining a rapid cooling patch made of a gel material. The prepared rapid cooling patch is black, including a microscopic rough surface (which can be called the "back") and a smooth surface (which can be called the "front") arranged back to back. The smooth surface has a higher adhesion to the skin, and the microscopic rough surface can evaporate faster when placed in the air. In air at 28 degrees and 50% humidity, its mass becomes 67% of the original mass after 1 hour, which shows that the volatilization efficiency of the hydrogel with a microscopic rough structure is higher than that of the hydrogel with smooth surfaces on both sides.
[0035] When using, tear off the waterproof packaging materials on both sides of the rapid cooling patch. Figure 2 As shown, the smooth surface fits on the skin, and the thermal conductive filler can form a connected network inside the gel material. This network extends from the bottom of the patch close to the skin to the surface with a micro-rough structure. Since the thermal conductive filler has a high thermal conductivity, it can quickly bring the heat generated on the skin to the back, and then through the high specific surface area on the back and the volatilization and heat absorption of the azeotropic solvent, the heat is quickly dissipated into the environment, thereby quickly reducing the temperature. According to measurements, in 28 degrees and 50% humidity air, the temperature can be reduced by more than 8 degrees in 2 minutes using this fast cooling patch.
[0036] In a comparative example, water is used as a solvent for preparing a gel material, hydroxyethyl methacrylate and polyethylene glycol 600 acrylate are used as polymer matrices, menthol and glycerol are added as additives, and photoinitiator 1173 is used to initiate acrylate curing. Among them, the mass of the solvent is taken as 10 parts, 2 parts of hydroxyethyl methacrylate, 0.1 parts of polyethylene glycol 600 acrylate, 0.1 parts of menthol, 1 part of glycerol, and 0.05 parts of photoinitiator 1173 are added. After the addition is completed, the mixture is uniformly mixed by mechanical stirring to obtain a mixed liquid. The slurry is placed in a pre-prepared silicone mold, the mold has a 1mm thick rectangular groove, so that the mixed liquid can completely fill the groove, and then covered with a transparent polyethylene terephthalate film, placed in a UV curing box, cured at a power of 100mW for 30 minutes, and then the cured material is taken out of the mold to obtain the desired comparative gel material. The prepared gel material is transparent, with a smooth surface on one side and a microscopic rough structure on the other side. The other steps of preparing the cooling patch are the same as those in Example 2. According to the measurement, in the air of 28 degrees and 50% humidity, the temperature of the cooling patch of the comparative example is only reduced by 3 degrees after 2 minutes.
[0037] In summary, the present invention discloses a gel-like material based on an azeotropic solvent, wherein the solvent used is an azeotropic solvent formed by water and an organic solvent, the polymer matrix used is a molecule that can be compatible with the azeotropic solvent to form a gel-like solid, and the filler used is a powder material with high thermal conductivity. Furthermore, additives can also be used in the raw materials, and the additives are substances that provide a cool feeling and reduce solvent volatilization. Based on the gel-like material, a microscopic rough structure can be prepared on one side of the gel-like material by a template method, and then a rapid gel cooling patch based on an azeotropic solvent is prepared. The rapid cooling patch is based on the synergistic effect of rapid volatilization of the azeotropic solvent, improvement of thermal conduction efficiency by thermally conductive fillers, and increase of volatilization and heat dissipation area by a microscopic rough surface, which greatly improves the cooling efficiency of the cooling patch.
[0038] Finally, it should be noted that although the embodiments of the present invention are described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments and application fields, and the above-mentioned specific embodiments are only illustrative and instructive, rather than restrictive. Under the guidance of this specification, a person of ordinary skill in the art can also make many forms without departing from the scope of protection of the claims of the present invention, all of which belong to the scope of protection of the present invention.
Claims
1. A gel material based on an azeotropic solvent, characterized in that: The gel material is formed by solidifying raw materials; the raw materials include an azeotropic solvent and a polymer matrix and a thermal conductive filler dispersed in the azeotropic solvent; the polymer matrix can form a three-dimensional cross-linked network in the azeotropic solvent; the azeotropic solvent is composed of two or more liquids, one of which is water, and the boiling point of the azeotropic solvent is lower than the boiling point of water.
2. The gel material according to claim 1, characterized in that: The other liquid in the azeotropic solvent is an organic solvent containing a hydroxyl group, a carboxyl group, a ketone group, or an ester group; preferably ethanol, n-butanol, isobutanol, ethyl acetate, or isopentanol.
3. The gel material according to claim 1, characterized in that: The ratio of each liquid in the azeotropic solvent is the ratio of the azeotropic point, or additional water is added at the ratio of the azeotropic point.
4. The gel material according to claim 1, characterized in that: Curing methods include cooling curing, heat curing, and light curing; When the curing method is cooling curing, the polymer matrix is selected from polyvinyl alcohol and gelatin materials; When the curing method is thermal curing, the polymer matrix is selected from small molecules with epoxy groups; When the curing method is light curing, various types of acrylic ester monomers are selected as the polymer matrix.
5. The gel material according to claim 1, characterized in that: The thermally conductive filler is at least one of carbon black, silver powder and liquid metal.
6. The gel material according to any one of claims 1 to 5, characterized in that: It also includes at least one first type of additive that provides a cooling sensation of gel, and / or at least one second type of additive that is used to reduce the evaporation rate of water.
7. The gel material according to claim 6, characterized in that: The first type of additives includes at least one of menthol, camphor, and borneol; the second type of additives includes at least one of glycerol and ethylene glycol that are miscible with water.
8. A cooling patch, characterized in that: The invention comprises a gel-like material based on an azeotropic solvent as claimed in any one of claims 1 to 7; the gel-like material has a microscopically rough first surface and a second surface arranged opposite to the first surface.
9. The cooling patch according to claim 8, characterized in that: The first surface is made by a template method, and the roughness of the first surface is Ra, 100nm≤Ra≤1000um; the first surface is a regular microstructure array, and the microstructure array is any one of a hemispherical array, a cylindrical array, and a rectangular array; or the first surface is composed of an irregular microstructure.
10. The cooling patch according to claim 8 or 9, characterized in that: It also includes a waterproof packaging material attached to the first surface and the second surface of the gel material; the waterproof packaging material includes at least one of a polypropylene film and a polyethylene terephthalate film.